The Relationship between the Educational Background and Training of Madrasah Principals and Change Management and Madrasah Excellence - Wahyudi, Muhammad Hirsan; Hariadi, Hariadi; Muhammad, Muhammad; Agus, Agus Hadian (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study examines the relationship between the educational background of madrasah principals and the training they have attended, with the management of change and the excellence of the madrasahs they manage. Based on a literature review, there is a relationship between the educational background of madrasah principals and the training they have attended, with the quality and quality of the management of the madrasahs they lead. This study aims to provide data analysis related to the relationship between the quality of madrasah principals based on their educational background and the training they have attended; with the excellence and quality of the madrasahs they manage. This study used a library research method. This research falls into the qualitative category, namely research that produces descriptive data in the form of written words. Based on the results of this study, data was obtained that the ability of the madrasah principal in improving the excellence of human resources in the madrasah he manages, his ability to innovate, the excellence of the madrasah, improving the quality of the curriculum, and the excellence of student achievement are directly related to the quality of a principal. The ability of the principal is determined by his educational background and how often he conducts training to upgrade his competence.